Secondary ozone peaks in the troposphere over the Himalayas - N. Ojha; A. Pozzer; D. Akritidis; J. Lelieveld (Atmospheric Chemistry and Physics, 2017)
Layers with strongly enhanced ozone concentrations in the middle–upper troposphere, referred to as secondary ozone peaks (SOPs), have been observed in different regions of the world. Here we use the global ECHAM5/MESSy atmospheric chemistry model (EMAC) to (i) investigate the processes causing SOPs, (ii) explore both their frequency of occurrence and seasonality, and (iii) assess their effects on the tropospheric ozone budget over the Himalayas. The vertical profiles of potential vorticity (PV) and a stratospheric ozone tracer (O 3 s) in EMAC simulations, in conjunction with the structure of SOPs, suggest that SOPs over the Himalayas are formed by stratosphere-to-troposphere transport (STT) of ozone. The spatial distribution of O 3 s further shows that such effects are in general most pronounced in the northern part of India. Model simulated ozone distributions and backward air trajectories show that ozone rich air masses, associated with STT, originate as far as northern Africa and the North Atlantic Ocean, the Middle East, as well as in nearby regions in Afghanistan and Pakistan, and are rapidly (within 2–3 days) transported to the Himalayas. Analysis of a 15-year (2000–2014) EMAC simulation shows that the frequency of SOPs is highest during the pre-monsoon season (e.g. 11 % of the time in May), while no intense SOP events are found during the July–October period. The SOPs are estimated to enhance the tropospheric column ozone (TCO) over the central Himalayas by up to 21 %.